2022
DOI: 10.1080/22423982.2021.2024679
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Assistance Programs on Indigenous Ways of Life in 12 Rural Remote Western Alaska Native Communities: Elder Perspectives Shared in Formative Work for the “Got Neqpiaq?” Project

Abstract: For more than 50 years, government programmes in the USA have been in place to help those in need have consistent access to food and education. However, questions have surfaced regarding whether or not these support impact traditional ways, such as cultural activities, food preferences, and overall health, particularly for Indigenous populations. In this paper, we share insights voiced by Alaska Native Elders in the Yukon-Kuskokwim region of Alaska and their perceptions of regulations, assistance, and the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This could be due to cultural norms of having a negative association attached to food stamps. A negative association with food assistance has been reported in interviews in other rural communities in Alaska due to the belief that food assistance programmes may negatively impact younger people’s motivation or the need for traditional methods of getting food [ 23 ]. Additionally, it was found that there were no school or tribal gardens in the communities, although other types of community gardens were considered to be important.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to cultural norms of having a negative association attached to food stamps. A negative association with food assistance has been reported in interviews in other rural communities in Alaska due to the belief that food assistance programmes may negatively impact younger people’s motivation or the need for traditional methods of getting food [ 23 ]. Additionally, it was found that there were no school or tribal gardens in the communities, although other types of community gardens were considered to be important.…”
Section: Discussionmentioning
confidence: 99%
“…Mucioki et al [ 35 ] and Pindus et al [ 33 ] reported on the FDPIR, which was established to specifically offer food assistance to rural First Nations communities. Although concerns have been raised around the impact on government programs on First Nations traditional ways [ 56 ], the monthly food boxes were shown to be a major food supply for many food-insecure families and communities. A key lesson is that a more “food sovereign” approach and integrating traditional foods may enhance food security and effectively address the needs of communities [ 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“… 25 Examining Pathways from Food Insecurity to Safer Sex Efficacy Among Northern and Indigenous Adolescents in the Northwest Territories, Canada [ 60 ] Food insecurity in Northwest Territories adolescents indirectly affects their sexual well-being, emphasizing the need for holistic interventions addressing sexual and mental health in the context of poverty. 26 Impact of Assistance Programs on Indigenous Ways of Life in 12 Rural Remote Western Alaska Native Communities: Elder Perspectives Shared in Formative Work for the “Got Neqpiaq?” Project [ 61 ] Alaska Native Elders express concerns about the impact of government assistance on Indigenous culture, calling for considerations in meeting food security and education needs without disrupting traditional practices. 27 The use of traditional climate knowledge by the Iraya Mangyans of Paluan, Mindoro, Philippines [ 62 ] Iraya Mangyans possess rich traditional climate knowledge (TCK), derived mostly from nature observations.…”
Section: Table A1mentioning
confidence: 99%